Montagem e tecnologia : efeitos visuais transição como pontuadores da narrativa audiovisual - Carvalho, Vinicius Augusto (2017)
The study proposes the mapping of transition visual effects (fade, dissolve, wipe and cluster), also called visible film punctuation in feature films in order to investigate whether the 1990s technological revolution has impacted the use of these effects in the film editing. Considering the entry of digital nonlinear editing through computers in the post-production process, due to the advent of digital technology and softwares that represent a milestone in the history of film editing, this research aims to analyze the frequency of the use of transition visual effects as a consequence of the introduction of digital editing in the film industry. The methodological process of analysis adopted in this research was the model of Perceptual Textual Analysis of Christian Metz (2004) that suggests that it is necessary to describe what is seen (film deconstruction) before seeking relationships and interpretations for the phenomena. The research features as its corpus all 83 Best Film Editing Academy Award-winning films from the Academy of Motion Picture Arts and Sciences in the United States, from 1935 to 2017. This dissertation deals with the history of editing and its technologies, details each one of the transition effects and through graphs and statistical inferences it seeks to promote some reflections on the use of visible punctuation in audiovisual products